PENGUATAN LAYANAN POSYANDU MELALUI PEMBERIAN SUPLEMENTASI DAN PEMERIKSAAN KESEHATAN DASAR DI DESA PEPELEGI - Rahmadani, Evi Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Community-based primary healthcare services through Pos Pelayanan Terpadu (Posyandu) are a strategic effort to improve public health, particularly among mothers, children, and the elderly. This community service aims to strengthen Posyandu services through supplementation and basic health examinations to enhance early risk detection and overall health status in Pepelegi Village. The interventions include vitamin A supplementation, deworming medication for children under five, and iron tablets, along with simple health checks such as blood pressure, weight, and height measurements. The method used is Asset-Based Community Development (ABCD), which optimizes local resources including posyandu cadres, village midwives, officials, and family participation. The implementation involves active community engagement. The results show that regular supplementation helps improve hemoglobin levels and increases awareness of routine health check-ups. In addition, this activity supports the optimization of Posyandu functions as promotive and preventive services. Therefore, integrated and simple interventions can positively improve community health quality at the village level.